Digital platforms for facilitating access to research infrastructures (Paris, 2017)
"Shared research infrastructures are playing an increasingly important role in most scientific fields and represent a significant proportion of the total public investment in science. Many of these infrastructures have the potential to be used outside of their traditional scientific domain and outside of the academic community but this potential if often not fully realised.  A major challenge for potential users (and for policy-makers) is simply identifying what infrastructures are available under what conditions. This report includes an analysis of 8 case studies of digital platforms that collate information and provide services to promote broader access to, and more effective use of, research infrastructures. Although there is considerable variety amongst the cases, a number of key issues are identified that can help guide policy-makers, funders, institutions and managers, who are interested in developing or contributing to such platforms."